Reserve site selection for data‐poor invertebrate fisheries using patch scale and dispersal dynamics: a case study of sea cucumber (Cucumaria frondosa). Issue 5 (3rd June 2013) - Shackell, Nancy L.; Brickman, David W.; Frank, Kenneth T.
ABSTRACT: Globally, management decisions for recently established invertebrate fisheries are based on limited information. The negative consequences are being realized as now at least one‐third of invertebrate fisheries are over‐exploited, collapsed or closed. Management of a fishery should be based on abundance and productivity data. This information is often unavailable but in some jurisdictions, spatial distributions are known. A methodology for designating a network of reserves for sedentary invertebrates, using sea cucumber ( Cucumaria frondosa ) on the Scotian Shelf, Canada is proposed, as a case study. It is assumed that there is a positive relationship between spawner density and per capita population growth rate in sedentary broadcast spawners and that fertilization success declines rapidly at low densities. Protection of high‐density habitat would safeguard critical spawner density, especially when the critical density is unknown. Using spatial distribution, a method to identify size and location of reserves designed to protect high‐density habitat was developed. First, geographically distinct regional‐scale clusters are identified. Within clusters, the characteristic patch scale was determined through spatial autocorrelation analysis. The size of reserves can be set as 50% of each high‐density patch based on an appropriate risk‐averse approach. The allocation of reserve size and location is not dependent on results of a numerical circulation model. However, the analysis was refined by using one to predict larval drift patterns, and connectivity among patches. Reserve boxes were then designated to safeguard from 30 to 65% of each high‐density patch. Marine reserves do not work if inappropriately sited. In the absence of any other information, it is argued that siting reserves on high‐density areas is an essential and appropriate approach to data‐poor invertebrate fisheries management. A high percentage of each high‐density patch could serve as risk‐averse 'spatial management' reference points, and could be modified once replenishment rates are known. Copyright © Her Majesty the Queen in Right of Canada 2013